Different responses of growth and physiology to warming and reduced precipitation of two co-existing seedlings in a temperate secondary forest - Yuan, Junfeng; Yan, Qiaoling; Wang, Jing; Xie, Jin; Li, Rong (Frontiers in Plant Science, 2022)
Warming and precipitation reduction have been concurrent throughout this century in most temperate regions (e.g., Northeast China) and have increased drought risk to the growth, migration, or mortality of tree seedlings. Coexisting tree species with different functional traits in temperate forests may have inconsistent responses to both warming and decreased precipitation, which could result in a species distribution shift and change in community dynamics. Unfortunately, little is known about the growth and physiological responses of coexisting species to the changes in these two meteorological elements. We selected two coexisting species in a temperate secondary forest of Northeast China: Quercus mongolica Fischer ex Ledebour (drought-tolerant species) and Fraxinus mandschurica Rupr. (drought-intolerant species), and performed an experiment under strictly controlled conditions simulating the predicted warming (+2°C, +4°C) and precipitation reduction (-30%) compared with current conditions and analyzed the growth and physiology of seedlings. The results showed that compared with the control, warming (including +2°C and +4°C) increased the specific area weight and total biomass of F. mandschurica seedlings. These were caused by the increases in foliar N content, the activity of the PSII reaction center, and chlorophyll content. A 2°C increase in temperature and reduced precipitation enhanced root biomass of Q. mongolica, resulting from root length increase. To absorb water in drier soil, seedlings of both species had more negative water potential under the interaction between +4°C and precipitation reduction. Our results demonstrate that drought-tolerant species such as Q. mongolica will adapt to the future drier conditions with the co-occurrence of warming and precipitation reduction, while drought-intolerant species will accommodate warmer environments.